Gross anatomy and histology of the heart and great vessels of a leopard seal (Hydrurga leptonyx) - Díaz, Alejandro (2024)
Leopard seals (Hydrurga leptonyx) are an essential apex predator widely distributed in the Antarctic and sub-Antarctic waters of the Southern Hemisphere (Erickson et al., 1971; Kooyman, 1981; King, 1983a; Hückstädt, 2015; Ferrer, 2018; Staniland et al., 2018). The presence of leopard seals in northern Argentina is directly related to the northward dispersal of juveniles from the Antarctic pack ice (Rodríguez et al., 2003; Bastida et al., 2007). Descriptions of the macroscopic anatomy of the leopard seal heart are rare. To our knowledge, only one study has detailed the cardiac anatomy based on a single specimen of this species (Drabek, 1975), and other studies have presented histological descriptions with anatomic aspects of the heart in a few specimens (Gray et al., 2006). This work aims to contribute to the knowledge of the cardiovascular system of the leopard seal through the anatomical and histological description of the heart and great vessels in one specimen studied a few hours postmortem.